2022
DOI: 10.1039/d1fo04391a
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of food derived nutrients on cisplatin nephrotoxicity and its mechanism

Abstract: Platinum-based metal complexes especially cisplatin (cis-diamminedichloroplatinum II, CDDP) possesses strong anticancer properties and a broad anticancer spectrum. However, the clinical application of CDDP has been limited by its side effects...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 168 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that Pink1/Parkin-mediated mitophagy prevented oxaliplatin-induced kidney injury and cognitive impairment. [19][20][21] However, whether Pink1/Parkin-mediated mitochondrial autophagy can be activated to prevent oxaliplatin-induced demyelination needs to be further demonstrated. Therefore, the hypothesis of this study is that remyelination by ATSO is related to the improvement of mitochondrial function by the Pink1/Parkin mitophagy pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that Pink1/Parkin-mediated mitophagy prevented oxaliplatin-induced kidney injury and cognitive impairment. [19][20][21] However, whether Pink1/Parkin-mediated mitochondrial autophagy can be activated to prevent oxaliplatin-induced demyelination needs to be further demonstrated. Therefore, the hypothesis of this study is that remyelination by ATSO is related to the improvement of mitochondrial function by the Pink1/Parkin mitophagy pathway.…”
Section: Introductionmentioning
confidence: 99%